Fentanyl Iontophoretic Transdermal System for Acute-Pain Management After Orthopedic Surgery: A Comparative Study With Morphine Intravenous Patient-Controlled Analgesia. Issue 6 (1st November 2006) - Hartrick, Craig T.; Bourne, Michael H.; Gargiulo, Kathryn; Damaraju, C. V.; Vallow, Sue; Hewitt, David J.
Abstract : Background and Objectives: The fentanyl HCl iontophoretic transdermal system (ITS) has been demonstrated in clinical trials to be safe and effective for acute-pain management after several types of major surgery. The current study compared the efficacy, safety, and convenience of fentanyl ITS with morphine intravenous patient-controlled analgesia (IV PCA) for acute-pain management after unilateral total-hip replacement (THR). Methods: In this multicenter (52 sites), randomized, open-label, active-controlled, phase IIIb study, patients (n = 799) received fentanyl ITS (40 μg fentanyl [10-minute infusion/lockout], up to 6 doses/h) or morphine IV PCA (1-mg morphine bolus [5-minute lockout], up to 10 mg/h) after unilateral THR. The primary efficacy measure was success ratings ("excellent" or "good") on the patient global assessment (PGA) of the method of pain control in the first 24 hours. Pain intensity and adverse events were also assessed. Results: The PGA success ratings (83.0% v 82.2%; difference = 0.9%; 95% CI: −4.4% to 6.1%) and the mean last pain-intensity scores (3.0 v 3.0; difference = 0.0; 95% CI: −0.33 to 0.33) in the first 24 hours were statistically equivalent between fentanyl ITS and morphine IV PCA groups, respectively. The incidence of adverse events was similar between the groups. Conclusions: Results of this study demonstrate fentanyl ITS and a standard regimen of morphine IV PCA were comparable methods of pain control for management of acute postoperative pain after THR, on the basis of the PGA success ratings and pain intensity in the first 24 hours of treatment.